FEATURES OF ANESTHESIA AT URGENT OPERATIVE INTERVENTIONS IN PATIENTS WITH THORACOABDOMINAL INJURIES - E. P. Sorokin; A. I. Gritsan; S. V. Ponomarev; Ye. V. Shilyaeva (Медицинский вестник Юга России, 2016)
Objective: identify the most acceptable options of anesthesia at urgent operative interventions concerning thoracoabdominal injuries depending on hemodynamic variables. Materials and methods: a retrospective analysis of medical cards of 203 patients treated in a specialized departament  about thoracoabdominal injuries. The severity of injuries according to ISS was 21.2±7.0 points. We estimated the impact of different anesthesia methods on such hemodynamic parameters as mean arterial pressure, heart rate, Кerdo index, Allgower index. For statistical data processing we used the program Microsoft Office Excel 2007, as well as automatic calculators site www.medcalc.org. Results: in patients with thoracoabdominal injuries commonly used inhalation anesthesia. The choice of method of anesthesia is based on anesthesiology-operation risk and indicators of hemodynamics in the preoperative period. The most commonly observed unstable hemodynamics during anesthesia with ketamine and nitrous oxide, the least – during anesthesia with propofol and sevoflurane. At high values of Kerdo index is more likely to occur when stable hemodynamics using propofol and sevoflurane, at low values – when using nitrous oxide and ketamine. In terms of total intravenous anesthesia ketamine patients often required the use of drugs with inotropic effects. Conclusions: If thoracoabdominal trauma patients with a predominance of the sympathetic tone of the nervous system, treatment of choice is anesthetic management total intravenous anesthesia using ketamine. In patients with a predominance of activity of the parasympathetic nervous system is possible to use inhalation anaesthesia.